New forces at work : industry views critical technologies - Popper, Steven W., 1953- (Rand, 1998)
For the fourth in a series of inquiries into the state of critical technologies in the United States, the Office of Science and Technology Policy in the Executive Office of the President asked a RAND Critical Technologies Institute research team to engage business and industry leaders explicitly in a discussion of the issue of critical technologies by gathering private-sector views on what technologies are appropriate to consider under this rubric--and why. The primary substantive input was elicited through extended, detailed interviews conducted individually, usually with one firm's senior executive per session, on-site in most cases. This report presents an analysis of the information gained during the course of those interviews. The report presents and analyzes interviewees' responses to what technologies they consider to be critical to their firm or industry; explores the question of what "critical technology" means; reports interviewees' assessments of the status of U.S.
"This report was conducted by Rand's Critical Technologies Institute under Contract OPA-9215205."
"Supported by the Office of Science and Technology Policy."
"Critical Technologies Institute."
Keywords: Technology assessment -- United States.; Technologie -- Évaluation -- États-Unis.; POLITICAL SCIENCE -- Public Policy -- Economic Policy.; BUSINESS & ECONOMICS -- Government & Business.; BUSINESS & ECONOMICS -- Development -- Economic Development.; BUSINESS & ECONOMICS -- Development -- Business Development.; BUSINESS & ECONOMICS -- Structural Adjustment.; BUSINESS & ECONOMICS -- Development -- General.; Technology assessment; United States; Neue Technologie; Technikbewertung; USA; Technology - General.; Engineering & Applied Sciences.